Effects of IL-34 on Macrophage Immunological Profile in Response to Alzheimer's-Related Aβ42 Assemblies - Zuroff, Leah R.; Torbati, Tania; Hart, Nadav J.; Fuchs, Dieu-Trang; Sheyn, Julia; Rentsendorj, Altan; Koronyo, Yosef; Hayden, Eric Y.; Teplow, David B.; Black, Keith L.; Koronyo-Hamaoui, Maya (Frontiers in Immunology, 2020)
Interleukin-34 (IL-34) is a recently discovered cytokine that acts as a second ligand of the colony stimulating factor 1 receptor (CSF1R) in addition to macrophage colony-stimulating factor (M-CSF). Similar to M-CSF, IL-34 also stimulates bone marrow (BM)-derived monocyte survival and differentiation into macrophages. Growing evidence suggests that peripheral BM-derived monocyte/macrophages (BMMO) play a key role in the physiological clearance of cerebral amyloid β-protein (Aβ). Aβ42 forms are especially neurotoxic and highly associated with Alzheimer’s disease (AD). As a ligand of CSF1R, IL-34 may be relevant to innate immune responses in AD. To investigate how IL-34 affects macrophage phenotype in response to structurally defined and stabilized Aβ42 oligomers and preformed fibrils, we characterized murine BMMO cultured in media containing M-CSF, IL-34, or regimens involving both cytokines. We found that the immunological profile and activation phenotype of IL-34-stimulated BMMO differed significantly from those cultured with M-CSF alone. Specifically, macrophage uptake of fibrillar or oligomeric Aβ42 was markedly reduced following exposure to IL-34 compared to M-CSF. Surface expression of type B scavenger receptor CD36, known to facilitate Aβ recognition and uptake, was modified following treatment with IL-34. Similarly, IL-34 macrophages expressed lower levels of proteins involved in both Aβ uptake (triggering receptor expressed on myeloid cells 2, TREM2) as well as Aβ-degradation (matrix metallopeptidase 9, MMP-9). Interestingly, intracellular compartmentalization of Aβ visualized by staining of early endosome antigen 1 (EEA1) was not affected by IL-34. Macrophage characteristics associated with an anti-inflammatory and pro-wound healing phenotype, including processes length and morphology, were also quantified, and macrophages stimulated with IL-34 alone displayed less process elongation in response to Aβ42 compared to those cultured with M-CSF. Further, monocytes treated with IL-34 alone yielded fewer mature macrophages than those treated with M-CSF alone or in combination with IL-34. Our data indicate that IL-34 impairs monocyte differentiation into macrophages and reduces their ability to uptake pathological forms of Aβ. Given the critical role of macrophage-mediated Aβ clearance in both murine models and patients with AD, future work should investigate the therapeutic potential of modulating IL-34 in vivo to increase macrophage-mediated Aβ clearance and prevent disease development.